Težnje v slovaški književnosti na koncu 20. stoletja - Zajac, Peter (Slavistična revija, 2002)
The article presents the process if reitegration of Slovak literature after the political breakup in 1989, its new nationalistic ideologization on the onehand and the search for space in individual isolation on the other. The author is following the internal generational and intergenerational rearrangement of values, brought forth by the 1990's. The literature did not experience a momentous rupture, but rather just a shift of the cloddy layers. Slovak literature is dominated by two lines: the line of resistance, shown in ironic and autobiographic image in works of the older and middle generations, and the line of coolness in works by younger writers.
Keywords: culture; družbene spremembe; history of literature; kultura; literarna zgodovina; Slovak literature; slovaška književnost; vrednote